Decision-making method for vehicle longitudinal automatic driving based on reinforcement Q-learning. (30th May 2019) - Gao, Zhenhai; Sun, Tianjun; Xiao, Hongwei
In the development of autonomous driving, decision-making has become one of the technical difficulties. Traditional rule-based decision-making methods lack adaptive capacity when dealing with unfamiliar and complex traffic conditions. However, reinforcement learning shows the potential to solve sequential decision problems. In this article, an independent decision-making method based on reinforcement Q-learning is proposed. First, a Markov decision process model is established by analysis of car-following. Then, the state set and action set are designed by the synthesized consideration of driving simulator experimental results and driving risk principles. Furthermore, the reinforcement Q-learning algorithm is developed mainly based on the reward function and update function. Finally, the feasibility is verified through random simulation tests, and the improvement is made by comparative analysis with a traditional method.